Personal reflections … on over 50 years in computer simulation. Issue 2 (3rd March 2020) - Nance, Richard E.
ABSTRACT: The author's experiences over a span of more than 50 years are characterised as a journey. Early interests in computer system performance modelling, information storage and retrieval, and computer networks become secondary to research topics in computer simulation. Organisations, events, and, most important, people define the paths, waysides, excursions, side roads, and major stops along the way. Editorial positions constitute an enduring thread throughout the journey. Capturing and preserving the history of the modelling and simulation discipline, frequently a topical sojourn, emerges as a dominant activity in the latter years. Two evocative questions, based on the prediction of a prominent computing pioneer, conclude the paper. 1955 Oldsmobile Starfire (98 Convertible) GRAPHICAL ABSTRACT: